A combined approach to treat heparin-induced thrombocytopaenia before heart transplant. (6th November 2020) - Sandoval, Elena; Lozano, Miquel; Pereda, Daniel; Quintana, Eduard; Cid, Joan; García-Álvarez, Ana; Fernández-Cisneros, Alejandro; Castellá, Manuel
Abstract: Heparin-induced thrombocytopaenia (HIT) complicates the management of patients in need for mechanical circulatory support awaiting heart transplantation. The limited available treatment options are fraught with complications and limitations in their applicability. We report on the combined use of therapeutic plasma exchange therapy and intravenous immunoglobulin, used in 3 consecutive heparin-induced thrombocytopaenia-positive patients on temporary mechanical circulatory support awaiting urgent heart transplant. This combined approach allowed us to use heparin safely. Abstract : Heparin-induced thrombocytopaenia (HIT) is becoming more common in cardiovascular surgery patients as they are more exposed to multiple doses of heparin and physicians' awareness has also increased.